Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10144-015-0501-6
|View full text |Cite
|
Sign up to set email alerts
|

Density and distribution of soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae) in response to UV radiation

Abstract: Increasing ultraviolet radiation (UV) has led to greater interest in its current and potential effects on organisms, including herbivorous insects. Here we report the short-term effects of UV on soybean aphids (Aphis glycines Matsumura), a common phytophagous pest of soybeans. We used two complementary approaches to examine how modifying UV radiation affects this phloemfeeding herbivore via changes to soybean aphid densities and their within plant distribution. We found that artificially adding UV in a lab set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
2
7
0
1
Order By: Relevance
“…However, we did measure the response of A. glycines' distribution on all of the soybean varieties. Soybean leaves have been observed blocking approximately 94% of ultra violet (UV) rays in a lab setting where 6-12% of the A. glycines population was found on the tops of leaves, 34-45% on the underside of leaves, and the remaining on stems and/or new growth (Burdick et al 2015). Our data showed that A. glycines distribution was in agreement with the majority on the leaves (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…However, we did measure the response of A. glycines' distribution on all of the soybean varieties. Soybean leaves have been observed blocking approximately 94% of ultra violet (UV) rays in a lab setting where 6-12% of the A. glycines population was found on the tops of leaves, 34-45% on the underside of leaves, and the remaining on stems and/or new growth (Burdick et al 2015). Our data showed that A. glycines distribution was in agreement with the majority on the leaves (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…brassicae on broccoli plants [ 6 , 22 , 25 ]. In another study, UV-A treatments reduced the reproduction of soybean aphids [ 36 ]. Illumination of Brussels sprout plants with additional LED-generated UV-A radiation (259 kJ m -2 d -1 ) in a greenhouse increased the concentrations of 3-indolylmethyl glucosinolate in the plants and reduced the fecundity of B .…”
Section: Discussionmentioning
confidence: 99%
“…Door weg te kruipen, bijvoorbeeld door zich te vestigen aan de onderkant van het blad, kunnen plagen zich beschermen tegen de schadelijke UV-B straling (e.g. Burdick et al 2015). Van deze gegevens is door Japanse onderzoekers gebruikgemaakt door het combineren van UV-B lampen met reflecterende doeken ('flash-spun nonwoven fabric sheets') (Sakai andOsakabe 2010, Tanaka et al 2016).…”
Section: Effecten Van Lichtspectrum Op Plagenunclassified